Monitoring Physiological Changes in Haloarchaeal Cell during Virus Release - Svirskaitė, Julija (Viruses, 2016)
The slow rate of adsorption and non-synchronous release of some archaeal viruses have hindered more thorough analyses of the mechanisms of archaeal virus release. To address this deficit, we utilized four viruses that infect Haloarcula hispanica that represent the four virion morphotypes currently known for halophilic euryarchaeal viruses: (1) icosahedral internal membrane-containing SH1; (2) icosahedral tailed HHTV-1; (3) spindle-shaped His1; and (4) pleomorphic His2. To discern the events occurring as the progeny viruses exit, we monitored culture turbidity, as well as viable cell and progeny virus counts of infected and uninfected cultures. In addition to these traditional metrics, we measured three parameters associated with membrane integrity: the binding of the lipophilic anion phenyldicarbaundecaborane, oxygen consumption, and both intra- and extra-cellular ATP levels.